Functional properties of cassava tapioca grits - Eke, J.; Achinewhu, S.C.; Sanni, Lateef O. (Informa UK Limited, 2010)
This study investigated the functional properties of tapioca grits produced from wet starches from 39 different cassava varieties (36 cassava mosaic disease resistant varieties CMD clones and 3 checks TMS 30572, 4(2) 1425 and 82/00058). There were significant differences (p < 0.05) for functional properties of tapioca grits from different cassava varieties. Dispersibility of tapioca ranged from 6–29%, water absorption capacity (WAC) ranged from 415.13–595.26%, swelling power ranged from 20.76–26.92%, solubility index ranged from 4.04–20.42%, color intensity ranged from 87.79–92.09%. Granule size of pre-gelatinized tapioca ranged from 12.50–22.50 mm. Significant differences (p < 0.05) were obtained on the effect of cassava varieties, viscometer speeds and temperature of tapioca meal. The viscosity of the tapioca meal decreased (37.90–0.72 Pa.s) with increasing shear rates at both 30 and 40o C, but higher for lower temperature respectively. Tapioca meal produced from cassava variety M98/0028 had the highest viscosity 37.90 Pa.s at 13.66 (s-1).